The Effect of Ultrasound and Core Stability Exercise on Increasing Lower Back Functionality in Adolescents - Pertiwi, Jasmine Kartiko; Ghufroni, Afif (Interest : Jurnal Ilmu Kesehatan, 2024)
Background: Myogenic low back pain is a disorder characterized by pain in the lower back. Low back pain can have an impact on impaired functional ability. Some of the factors causing functional disorders are physiological factors, poor body posture, and unergonomic work postures. Adolescents are a group that is vulnerable to experiencing functional decline in the lower back due to pain in the lower back as a result of the demands of activity during the learning process, by spending most time sitting, and having busy learning schedules, which make physical activity tend to be low, which can result in decreased lower back functionality. The aim of the study is to determine the effect of ultrasound and core stability exercise on functional abilities in sufferers of myogenic low back pain in adolescents. Methods: The research design was pre-experimental with a one-group pre-and post-test design. From a total population of around 100, after simple random sampling, 57 subjects were obtained with measurements using the Oswestry Disability Index (ODI). Results: The results of the normality test data analysis using the Kolmogorov-Smirnov test, ODI pre-test 0.072, and ODI post-test 0.157, and for hypothesis testing using the paired sample t-test P 0.000, so that there is a significant difference. Conclusion: The clinical implications could be the influence of providing ultrasound and core stability exercises on improving lower back function in adolescents. So the hypothesis is accepted.